(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
COVID-19 is a highly infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-COV-2). Recently COVID -19 radiological literature focuses primarily on CT scan findings which are more sensitive (about 97%) and specific than chest x-ray. But it has to be remembered that performing CT scan is not easy during this pandemic situation. So, the aim of the study was to analyze the chest x-ray severity scoring system and its association with outcome in a young adult patient with COVID-19. This cross-sectional study was carried out from September 15 to December 31 2020 in the COVID unit of BSMMU and it included 100 RT-PCR positive COVID-19 patients according to selection criteria. Chest x-ray postero-anterior view was done in the radiology department of BSMMU. Each patient’s chest x-ray was examined by a radiologist and a pulmonologist with experience of 10 years. Radiological scoring was done by using a scoring system. All patients were followed after 20 days from the first presentation to see the outcome. Out of 100 patients, 73 patients (73%) needed hospital admission, 33(33%) patients were hospitalized but did not developed sepsis, 29 (29%) patient developed sepsis, 10(10%) patient needed ICU support among them 2 patients got intubation. 1(1%) patient was dead. Radiological score ≥ 4 was associated with increased risk of hospitalization. (Area under curve = 0.956). Score ≥ 5 was associated with increased risk of sepsis; score ≥7 was associated with increased risk of ICU admission. (p-value<0.001). BSMMU J 2021; 14 (COVID -19 Supplement): 30-35